Production of urban space in small cities: a view on the city of Buriti dos Lopes, Piauí - Frota, Jessica Cristina Oliveira; Silva, Anayana de Sousa (Geosaberes; Vol 10 No 21 (2019): May - August, 2019)
The urban space is produced through the action of some agents responsible for the production of this space, these in turn are characterized as owners of the means of production, landowners, real estate developers, state and excluded social groups. These agents act differently when it comes to small, medium or large cities. The present research aims to understand how the production of urban space occurs from the perspective of a small city and identify the main producers of this process, since small cities make up the majority of Brazilian cities. As methodological procedures, bibliographical research, interviews with unions and associations and observation "in loco" were used, in order to validate the proposed objectives. Through the analysis of the production process of the urban space of the city of Buriti dos Lopes-PI, it can be verified that the performance of some producers agents, in the context of a small city, is restricted due to the socioeconomic peculiarities of A small city. From the agents under discussion, it was verified from this research that the State is the most active in the production of urban space in cities such as Buriti dos Lopes-PI, especially in the municipal sphere.